Barium ferrite absorbent, high-frequency wave-absorbing coating, preparation method of high-frequency wave-absorbing coating and wave-absorbing coating
Through the preparation method of barium ferrite absorber, combined with the addition of nano-SiO2, nano-ferric oxide and graphene, the problem of limited application range of existing high-frequency absorbing coatings is solved, and the application range of high-frequency absorbing coatings is realized. Low weight, high stealth performance characteristics, and reduced production costs.
Patent Information
- Application Number
- CN202411466454.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-24
AI Technical Summary
The application range of existing high-frequency absorbing coatings is limited. Due to the large thickness, high surface density and heavy weight, the cost increases and the film thickness and weight requirements cannot be met in some scenarios.
The preparation method of iron oxygen absorbers is adopted, and the nano -SiO2 and a small amount of nano -tetraxidine oxide and graphene are added during the splash and sintering process by mixed with nickel oxide, nickel oxide, cobalt oxide, zinc oxide, zinc oxide, and iron oxide. The dielectric loss and magnetic loss of suction coatings increase the frequency width range.
The characteristics of the coating of high -frequency suction coatings, low surface density, light weight, light weight, good stealth performance, while reducing costs, simple process control, suitable for stable production.
Smart Images

Figure CN119349646A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of absorbing materials, and in particular to a barium ferrite absorber, a high-frequency absorbing paint, a preparation method thereof, and an absorbing coating. Background Art
[0002] At present, with the development and progress of weapons and equipment, detection technology and stealth technology promote each other's development. As the working frequency of high-precision detection radar develops towards high frequency, the frequency can reach 40GHz, and the corresponding stealth technology also develops towards high-frequency bands. In addition to reducing the radar cross-sectional area by external design, absorbing materials are an indispensable and important means in radar stealth technology. At present, in the research of M-type barium ferrite, high-valent ions are mainly added to achieve better absorbing performance at high frequencies (26-40GHz); and the research on W-type barium ferrite shows that the better absorbing frequency bands are mostly concentrated in the lower frequency bands (4-18GHz); and the existing reported thicknesses are all over 2mm, resulting in a large coating weight and high surface density, which limits practical applications.
[0003] The existing patent publication number CN103102867A discloses a metal ion-doped barium ferrite absorbing powder and a preparation method thereof, using a tetravalent or higher metal ion (such as Ti 4+ ) doped M-type barium ferrite to prepare the absorbing powder. In Example 1, BaFe 11.4 Ti 0.6 O 19 When the sample thickness is 2.8mm, an absorption peak appears at 29.3GHz and 38.9GHz in the frequency range of 26.5~40GHz, and the absorption bandwidth of RL<-10dB is about 11.8GHz. According to its test method, the mass ratio of barium ferrite absorbing powder material and paraffin is 8:3. Based on the density of M-type barium ferrite is 5.28g / cm 3 、Paraffin density is 0.9g / cm 3 Calculation, 2.8mm thickness 1m 2 The weight of the square sample is about 8.8kg (i.e. the surface density is 8.8kg); when it is made into a coating, the density is 1.1g / cm 3 If epoxy resin is used to replace paraffin wax, the surface density will reach 9.7kg, which is seriously overweight. In actual application, it will not only lead to a significant increase in costs, but also fail to meet the needs of scenes with strict requirements on film thickness and weight, limiting the scope of application. Summary of the invention
[0004] The main purpose of the present invention is to provide a barium ferrite absorber, a high-frequency absorbing coating and a preparation method thereof and an absorbing coating, aiming to solve the technical problem that the application scope of existing high-frequency absorbing coatings is limited.
[0005] To achieve the above object, the present invention provides a barium ferrite absorber, the chemical formula of the absorber is Ba(Ni x Co y Zn z )Fe 16 O 27 , where x+y+z=2, 1≤x≤2, 0≤y<1, 0≤z<0.5, x≥1>y>z.
[0006] In addition, in order to achieve the above object, the present invention also provides a method for preparing a barium ferrite absorber, the method comprising the following steps:
[0007] Step 11, mixing barium oxide BaO, nickel oxide NiO, cobalt oxide Co2O3, zinc oxide ZnO and iron oxide Fe2O3 in a preset mass ratio, and dry-milling for 2-5 hours to obtain ball-milled powder, wherein a preset amount of nano-SiO2 and Ba, Ni, Co in the ball-milled powder are successively added during the ball-milling process. 、 The atomic ratio of Zn and Fe elements is 1:(1-2):(0-1):(0-0.5):16;
[0008] Step 12, pressing the ball-milled powder in step 11 into a block, and placing it in a kiln at 1300-1400° C. in an air atmosphere for 2-5 hours to obtain a sintered block;
[0009] Step 13, mechanically crushing and screening the sintered block to obtain a barium ferrite absorbent.
[0010] Optionally, in step 13, air flow screening treatment is adopted, and the particle size D50 of the barium ferrite absorber is controlled to be ≤25 μm.
[0011] Optionally, the Ba, Ni, Co in the ball-milled powder 、 The atomic ratio of Zn and Fe elements is 1:(1.2-1.7):(0.2-0.8):(0-0.2):16.
[0012] Optionally, in step 11, the mass of the added nano-SiO2 is 0.01-0.05% of the total mass of the mixture of barium oxide BaO, nickel oxide NiO, cobalt oxide Co2O3, zinc oxide ZnO and iron oxide Fe2O3.
[0013] In addition, in order to achieve the above object, the present invention also provides a method for preparing a high-frequency absorbing coating, comprising the following steps:
[0014] Step 21, adding epoxy resin, ferroferric oxide, and graphene into a stirring barrel according to a preset ratio, adding anhydrous ethanol and stirring for 0.5 h, and then ball milling for 1-2 h using a horizontal sand mill to obtain an initial slurry;
[0015] Step 22, adding the initial slurry into a mixer, adding the barium ferrite absorber described above according to a preset ratio, and mechanically stirring for 2-5 hours to obtain a high-frequency absorbing coating, wherein the mass ratio of the barium ferrite absorber, epoxy resin, nano-ferroferric oxide and graphene is (80-88): (10-18): (0.1-2): (0.1-0.2).
[0016] Optionally, the mass of the anhydrous ethanol in step 21 is 50-60% of the total mass of the barium ferrite absorber, the epoxy resin, the nano-ferroferric oxide and the graphene.
[0017] In addition, in order to achieve the above purpose, the present invention also provides a high-frequency absorbing coating prepared by the above method.
[0018] Optionally, the viscosity of the high-frequency absorbing coating is 300-2000 mPa·s.
[0019] In addition, in order to achieve the above-mentioned purpose, the present invention also provides an absorbing coating, which is obtained by spraying the above-mentioned high-frequency absorbing coating on the surface of the target substrate, with a spraying thickness of 0.85 mm, and the reflection loss of the absorbing coating at 27 to 40 GHz is lower than -8 dB.
[0020] Beneficial effects:
[0021] (1) The high-frequency absorbing coating of the present invention has the characteristics of thin coating thickness, low surface density, light weight and good coating stealth performance at a high frequency of 27-40 GHz.
[0022] (2) Compared with the existing Co-Zn-W type barium ferrite whose absorption band is mainly concentrated below 18 GHz, the barium ferrite absorber in the present invention greatly reduces the amount of Co and Zn added, and increases the amount of Ni added to increase the absorption frequency of the high-frequency absorbing coating subsequently prepared. The principle is that Zn is a non-magnetic element, and excessive addition of Zn 2+ may affect the magnetic properties of the W phase, while Ni 2+ Than Ni 3+ The stability is good, and the amount of Ni added can be increased to achieve the magnetic properties of high Ni-type W-type barium ferrite. And on the basis of the NiW-type barium ferrite absorber, a small amount of nano-iron tetroxide and graphene are added, and the dielectric loss and magnetic loss of the coating are adjusted by utilizing the ferromagnetic characteristics of the spinel structure of Fe3O4 and the large flat shape and high conductivity characteristics of graphene, and the frequency width range of the absorbing coating is appropriately increased. Compared with the method of adding precious metals in the prior art, the present invention does not need to add more precious high-valent ions, thereby effectively reducing costs, simplifying process control, and achieving stable production. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a reflection loss-frequency diagram of a coating obtained after spraying the high-frequency absorbing coating of the first embodiment of the method for preparing the high-frequency absorbing coating of the present invention;
[0024] Figure 2 A schematic diagram of reflection loss-frequency of a coating obtained after spraying the high-frequency absorbing coating according to the second embodiment of the method for preparing the high-frequency absorbing coating of the present invention;
[0025] Figure 3 A schematic diagram of reflection loss-frequency of a coating obtained after spraying the high-frequency absorbing coating according to the third embodiment of the method for preparing the high-frequency absorbing coating of the present invention;
[0026] Figure 4 This is a schematic diagram of reflection loss-frequency of a coating obtained after spraying the high-frequency absorbing coating according to the fourth embodiment of the method for preparing the high-frequency absorbing coating of the present invention.
[0027] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0028] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.
[0029] The present invention provides a method for preparing a barium ferrite absorber, the method comprising the following steps:
[0030] Step 11, mix barium oxide BaO, nickel oxide NiO, cobalt oxide Co2O3, zinc oxide ZnO and iron oxide Fe2O3 in a preset mass ratio, and dry ball-mill for 2-5 hours to obtain ball-milled powder, wherein a preset amount of nano-SiO2 is added successively during the ball-milling process, and the mass of the added nano-SiO2 is 0.01-0.05% of the total mass of the barium oxide BaO, nickel oxide NiO, cobalt oxide Co2O3, zinc oxide ZnO and iron oxide Fe2O3 after mixing.
[0031] Step 12, pressing the ball-milled powder in step 11 into a block, and placing it in a kiln at 1300-1400° C. in an air atmosphere for 2-5 hours to obtain a sintered block;
[0032] Step 13, mechanically crushing and screening the sintered block to obtain a barium ferrite absorbent, wherein the chemical formula of the absorbent is Ba(Ni x Co y Zn z )Fe 16 O 27 , where x+y+z=2, 1≤x≤2, 0≤y<1, 0≤z<0.5, x≥1>y>z, and Ba, Ni, Co in the ball-milled powder、 The atomic ratio of Zn and Fe is 1:(1-2):(0-1):(0-0.5):16. Preferably, the Ba, Ni, Co 、 The atomic ratio of Zn and Fe elements is 1:(1.2-1.7):(0.2-0.8):(0-0.2):16.
[0033] Furthermore, in step 13, the air flow screening treatment is adopted, and the particle size D50 of the barium ferrite absorber is controlled to be ≤25 μm.
[0034] Furthermore, the present invention also provides a method for preparing a high-frequency absorbing coating, comprising the following steps:
[0035] Step 21, adding epoxy resin, ferroferric oxide, and graphene into a stainless steel stirring barrel according to a preset ratio, adding anhydrous ethanol and stirring for 0.5 hours, and then using a horizontal sand mill for ball milling for 1-2 hours to obtain an initial slurry, wherein the mass of the added anhydrous ethanol is 50-60% of the total mass of the barium ferrite absorber, epoxy resin, nano-ferroferric oxide and graphene.
[0036] Step 22, add the initial slurry into a mixer, add the barium ferrite absorber according to a preset ratio, and mechanically stir for 2-5 hours to obtain a high-frequency absorbing coating, wherein the mass ratio of the barium ferrite absorber, epoxy resin, nano-ferroferric oxide and graphene is (80-88): (10-18): (0.1-2): (0.1-0.2). And the viscosity of the high-frequency absorbing coating is 300-2000 mPa·s.
[0037] Furthermore, the prepared high-frequency absorbing coating is sprayed onto the surface of the target substrate and dried at room temperature to form a high-frequency absorbing coating with a spraying thickness of 0.85-1mm. The coating is then tested for reflection loss, and it is finally found that the reflection loss of the absorbing coating at 27-40GHz is less than -8dB, and the coating has the characteristics of thin thickness, low surface density, light weight, and good stealth performance.
[0038] The principle is that in the existing Co-Zn-W type barium ferrite, Zn 2+ The addition amount is higher than Co 2+ The addition amount of Zn is higher, and the absorption performance is better, which may be due to the addition of Co 3+ Co 2+ More stable, but when the amount of Co added is too much, some Co 2+ will be transformed into Co 3+ , which makes the performance difficult to control. At the same time, Zn is a non-magnetic element, and excessive addition of Zn 2+ may affect the magnetic properties of the W phase, while Ni 2+ Than Ni3+ The invention has good stability, can increase the amount of Ni added, realize the magnetic properties of high Ni type W type barium ferrite, and on the basis of Ni-W barium ferrite absorber, by adding a small amount of nano ferroferric oxide and graphene, the dielectric loss and magnetic loss of the coating are adjusted by utilizing the ferromagnetic characteristics of the spinel structure of Fe3O4 and the large flat shape and high conductivity characteristics of graphene, and the frequency width range of the absorbing coating is appropriately increased. Furthermore, the invention does not need to add more expensive high-valent ions, and the process control is simple, and stable production can be easily achieved. Finally, the absorbing coating has the characteristics of thin coating thickness, low surface density, light weight, and good coating stealth performance at a high frequency of 27-40GHz.
[0039] Furthermore, in order to better determine the specific performance of the above coating, the following is described in detail through specific examples:
[0040] Example 1
[0041] Preparation of Barium Ferrite Absorber
[0042] The raw materials of barium oxide BaO, nickel oxide NiO, cobalt oxide Co2O3, zinc oxide ZnO and iron oxide Fe2O3 are prepared according to Ba(Ni 1.2 Co 0.8 )Fe 16 O 27 After weighing, add it to a high-energy ball mill, add 0.05% nano-SiO2 as an auxiliary agent, and dry ball mill for 2 hours. Then press the obtained ball-milled powder into blocks, place it in an air atmosphere kiln for heating and sintering, and keep it at 1300℃ for 3 hours to obtain absorber sintered blocks; and mechanically crush the absorber sintered blocks, pass through air flow screening, and obtain barium ferrite absorber powder. After measurement, the particle size of the absorber powder is D50=25 microns.
[0043] Preparation of high frequency microwave absorbing coating
[0044] Epoxy resin, ferroferric oxide and graphene are added to a stainless steel mixing barrel according to a preset ratio, anhydrous ethanol is added and stirred for 0.5 hours, and then a horizontal sand mill is used for ball milling for 2 hours to obtain an initial slurry; the initial slurry is added to a mixer, barium ferrite absorber is added according to a preset ratio, and mechanical stirring is performed for 2 hours to obtain a high-frequency absorbing coating, and the viscosity of the high-frequency absorbing coating is 300mPa·s. Among them, the added mass fraction ratio of barium ferrite absorber, epoxy resin, ferroferric oxide and graphene is: barium ferrite absorber is 82%, epoxy resin is 17%, nano-ferroferric oxide Fe3O4 is 0.9%, graphene is 0.1%, and the mass of anhydrous ethanol is 50% of the total mass of barium ferrite absorber, epoxy resin, nano-ferroferric oxide and graphene.
[0045] Preparation of microwave absorbing coating
[0046] The high-frequency absorbing coating was sprayed on a 180*180mm aluminum alloy plate with a film thickness of about 0.85mm, and the reflection loss of the coating was tested. The results are as follows Figure 1 As shown in the figure, the reflection loss is better than -8dB in the range of 28.55 to 39.33GHz, 1m 2 The coating weight on the panel was 3.30 kg.
[0047] Example 2
[0048] Preparation of Barium Ferrite Absorber
[0049] The raw materials of barium oxide BaO, nickel oxide NiO, cobalt oxide Co2O3, zinc oxide ZnO and iron oxide Fe2O3 are prepared according to Ba(Ni 1.2 Co 0.7 Zn 0.1 )Fe 16 O 27 After weighing, add it to a high-energy ball mill, add 0.01% nano-SiO2 as an auxiliary agent, and dry ball mill for 5 hours. Then press the obtained ball-milled powder into blocks, place it in an air atmosphere kiln for heating and sintering, and keep it at 1300℃ for 3 hours to obtain a sintered block of the absorber; the sintered block of the absorber is mechanically crushed, and sieved through air flow to obtain barium ferrite absorber powder, and the particle size of the absorber powder is D50=18 microns.
[0050] Preparation of high frequency microwave absorbing coating
[0051] Epoxy resin, ferroferric oxide and graphene are added to a stainless steel mixing barrel according to a preset ratio, anhydrous ethanol is added and stirred for 0.5 hours, and then a horizontal sand mill is used for ball milling for 2 hours to obtain an initial slurry; the initial slurry is added to a mixer, barium ferrite absorber is added according to a preset ratio, and mechanical stirring is performed for 3 hours to obtain a high-frequency absorbing coating, and the viscosity of the high-frequency absorbing coating is 1000mPa·s. The added mass fraction ratio of barium ferrite absorber, epoxy resin, ferroferric oxide and graphene is: barium ferrite absorber is 88%, epoxy resin is 14%, nano-ferroferric oxide Fe3O4 is 0.9%, graphene is 0.1%, and the mass of anhydrous ethanol is 55% of the total mass of barium ferrite absorber, epoxy resin, nano-ferroferric oxide and graphene.
[0052] Preparation of microwave absorbing coating
[0053] The high-frequency absorbing coating was sprayed on a 180*180mm aluminum alloy plate with a film thickness of about 0.9mm, and the reflection loss of the coating was tested. The results are as follows Figure 2 As shown in the figure, the reflection loss is better than -8dB in the range of 28.29 to 40GHz, and the 1m 2 The coating weight on the panel was 3.03 kg.
[0054] Example 3
[0055] Preparation of Barium Ferrite Absorber
[0056] The raw materials of barium oxide BaO, nickel oxide NiO, cobalt oxide Co2O3, zinc oxide ZnO and iron oxide Fe2O3 are prepared according to Ba(Ni 1.5 Co 0.3 Zn 0.2 )Fe 16 O 27 After weighing, add it to a high-energy ball mill, add 0.01% nano-SiO2 as an auxiliary agent, and dry ball mill for 3 hours. Then press the obtained ball-milled powder into blocks, place it in an air atmosphere kiln for heating and sintering, and keep it at 1350℃ for 3 hours to obtain a sintered block of the absorber; the sintered block of the absorber is mechanically crushed, and sieved through air flow to obtain barium ferrite absorber powder, and the particle size of the absorber powder is D50=20 microns.
[0057] Preparation of high frequency microwave absorbing coating
[0058] Then, epoxy resin, ferroferric oxide, and graphene are added to a stainless steel mixing barrel in proportion, anhydrous ethanol is added and stirred for 0.5 hours, and then a horizontal sand mill is used for ball milling for 2 hours to obtain an initial slurry; the initial slurry is added to a mixer, barium ferrite absorber is added in proportion, and mechanical stirring is performed for 2 hours to obtain a high-frequency absorbing coating, and the viscosity of the high-frequency absorbing coating is 1500mPa·s. The added mass fraction ratio of barium ferrite absorber, epoxy resin, ferroferric oxide, and graphene is: barium ferrite absorber is 80%, epoxy resin is 14.6%, nano-ferroferric oxide Fe3O4 is 2%, graphene is 0.2%, and the mass of anhydrous ethanol is 60% of the total mass of barium ferrite absorber, epoxy resin, nano-ferroferric oxide, and graphene.
[0059] Preparation of microwave absorbing coating
[0060] The high-frequency absorbing coating was sprayed on a 180*180mm aluminum alloy plate with a film thickness of about 0.9mm, and the reflection loss of the coating was tested. The results are as follows Figure 3 As shown in the figure, the reflection loss is better than -8dB in the range of 32.56 to 40GHz, and the 1m 2 The coating weight on the panel was 3.05 kg.
[0061] Example 4
[0062] Preparation of Barium Ferrite Absorber
[0063] The raw materials of barium oxide BaO, nickel oxide NiO, cobalt oxide Co2O3, zinc oxide ZnO and iron oxide Fe2O3 are prepared according to Ba(Ni 1.7 Co0.2 Zn 0.1 )Fe 16 O 27 After weighing, add it to a high-energy ball mill, add 0.01% nano-SiO2 as an auxiliary agent, and dry ball mill for 3 hours. Then press the obtained ball-milled powder into blocks, place it in an air atmosphere kiln for heating and sintering, and keep it at 1400℃ for 5 hours to obtain a sintered block of the absorber; the sintered block of the absorber is mechanically crushed, and sieved through air flow to obtain barium ferrite absorber powder, and the particle size of the absorber powder is D50=15 microns.
[0064] Preparation of high frequency microwave absorbing coating
[0065] Epoxy resin, ferroferric oxide and graphene are added to a stainless steel mixing barrel in proportion, anhydrous ethanol is added and stirred for 0.5 hours, and then a horizontal sand mill is used for ball milling for 2 hours to obtain an initial slurry; the initial slurry is added to a mixer, barium ferrite absorber is added in proportion, and mechanical stirring is performed for 2 hours to obtain a high-frequency absorbing coating, and the viscosity of the high-frequency absorbing coating is 1500mPa·s. The added mass fraction ratio of barium ferrite absorber, epoxy resin, ferroferric oxide and graphene is: barium ferrite absorber is 85%, epoxy resin is 14.8%, nano-ferroferric oxide Fe3O4 is 0.1%, graphene is 0.1%, and the mass of anhydrous ethanol is 60% of the total mass of barium ferrite absorber, epoxy resin, nano-ferroferric oxide and graphene.
[0066] Preparation of microwave absorbing coating
[0067] The high-frequency absorbing coating was sprayed on a 180*180mm aluminum alloy plate with a film thickness of about 0.85mm, and the reflection loss of the coating was tested. The results are as follows Figure 4 As shown in the figure, the reflection loss is better than -8dB in the range of 26.5 to 40GHz, and the 1m 2 The coating weight on the panel was 3.34 kg.
[0068] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or system. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or system including the element.
[0069] The serial numbers of the above embodiments of the present invention are only for description and do not represent the advantages or disadvantages of the embodiments.
[0070] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A barium ferrite absorber, characterized in that: The chemical formula of the absorbent is Ba(Ni x Co y Zn z )Fe 16 O 27 , where x+y+z=2, 1≤x≤2, 0≤y<1, 0≤z<0.5, x≥1>y>z.
2. A method for preparing the barium ferrite absorber according to claim 1, characterized in that: The method comprises the following steps: Step 11, mixing barium oxide BaO, nickel oxide NiO, cobalt oxide Co2O3, zinc oxide ZnO and iron oxide Fe2O3 in a preset mass ratio, and dry-milling for 2-5 hours to obtain ball-milled powder, wherein a preset amount of nano-SiO2 and Ba, Ni, Co in the ball-milled powder are successively added during the ball-milling process. 、 The atomic ratio of Zn and Fe elements is 1:(1-2):(0-1):(0-0.5):16; Step 12, pressing the ball-milled powder in step 11 into a block, and placing it in a kiln at 1300-1400° C. in an air atmosphere for 2-5 hours to obtain a sintered block; Step 13, mechanically crushing and screening the sintered block to obtain a barium ferrite absorbent.
3. The method for preparing the barium ferrite absorbent according to claim 2, characterized in that: In step 13, airflow screening treatment is adopted, and the particle size D50 of the barium ferrite absorber is controlled to be ≤25 μm.
4. The method for preparing the barium ferrite absorbent according to claim 2, characterized in that: In step 11, the Ba, Ni, Co 、 The atomic ratio of Zn and Fe elements is 1:(1.2-1.7):(0.2-0.8):(0-0.2):
16.
5. The method for preparing the barium ferrite absorbent according to claim 2, characterized in that: In step 11, the mass of the added nano-SiO2 is 0.01-0.05% of the total mass of the mixture of barium oxide BaO, nickel oxide NiO, cobalt oxide Co2O3, zinc oxide ZnO and iron oxide Fe2O3.
6. A method for preparing a high-frequency absorbing coating, characterized in that: The following steps are involved: Step 21, adding epoxy resin, ferroferric oxide, and graphene into a stirring barrel according to a preset ratio, adding anhydrous ethanol and stirring for 0.5 h, and then ball milling for 1-2 h using a horizontal sand mill to obtain an initial slurry; Step 22, adding the initial slurry into a mixer, adding the barium ferrite absorber described in claim 1 according to a preset ratio, and mechanically stirring for 2-5 hours to obtain a high-frequency absorbing coating, wherein the mass ratio of the barium ferrite absorber, epoxy resin, nano-ferroferric oxide and graphene is (80-88): (10-18): (0.1-2): (0.1-0.2).
7. The method for preparing the high-frequency absorbing coating according to claim 6, characterized in that: The mass of the anhydrous ethanol in step 21 is 50-60% of the total mass of the barium ferrite absorber, epoxy resin, nano-ferroferric oxide and graphene.
8. A high-frequency radar absorbing coating prepared by the method of claim 6 or 7.
9. The high frequency absorbing coating according to claim 8, characterized in that: The viscosity of the high-frequency absorbing coating is 300-2000 mPa·s.
10. A radar absorbing coating, characterized in that: The absorbing coating is obtained by spraying the high-frequency absorbing coating in claim 8 or 9 onto the surface of the target substrate, with a spraying thickness of 0.85-0.9 mm, and the reflection loss of the absorbing coating at 27-40 GHz is lower than -8 dB.
Citation Information
Patent Citations
Metal ion doped barium ferrite wave absorbing powder and preparation method thereof
CN103102867A